2006
DOI: 10.1111/j.1440-1827.2006.01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Emmprin (basigin/CD147): Matrix metalloproteinase modulator and multifunctional cell recognition molecule that plays a critical role in cancer progression

Abstract: Emmprin (basigin, CD147) is a cell surface glycoprotein that belongs to the immunoglobulin superfamily. It is highly expressed on the surface of tumor cells and stimulates adjacent fibroblasts or tumor cells to produce matrix metalloproteinases. Moreover, it has recently been shown that emmprin also stimulates expression of vascular endothelial growth factor and hyaluronan, which leads to angiogenesis and anchorage-independent growth/multidrug resistance, respectively. These findings have made emmprin an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
224
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(235 citation statements)
references
References 81 publications
6
224
1
4
Order By: Relevance
“…It is highly expressed in tumor cells and stimulates adjacent fibroblasts or tumor cells to produce matrix metalloproteinases (MMPs). 23 CD147 is overexpressed in a number of carcinomas and is associated with tumor progression. 23,24 Previous findings have shown that CD147 promotes migration, invasion, and metastasis in cancer cells, enhancing the activity of MMPs by digesting the components of the extracellular matrix in breast cancer, oral squamous cell carcinoma, and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly expressed in tumor cells and stimulates adjacent fibroblasts or tumor cells to produce matrix metalloproteinases (MMPs). 23 CD147 is overexpressed in a number of carcinomas and is associated with tumor progression. 23,24 Previous findings have shown that CD147 promotes migration, invasion, and metastasis in cancer cells, enhancing the activity of MMPs by digesting the components of the extracellular matrix in breast cancer, oral squamous cell carcinoma, and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…23 CD147 is overexpressed in a number of carcinomas and is associated with tumor progression. 23,24 Previous findings have shown that CD147 promotes migration, invasion, and metastasis in cancer cells, enhancing the activity of MMPs by digesting the components of the extracellular matrix in breast cancer, oral squamous cell carcinoma, and ovarian cancer. [25][26][27] Sp1 was a eukaryotic transcriptional activator identified and involved in many physiological and pathological processes by regulating gene expression, which is affected by the rate of Sp1 protein synthesis, nuclear translocation, and DNAbinding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Sowohl die TransmembrandomĂ€ne mit 24 AS als auch die 40 AS umfassende zytoplasmatische DomĂ€ne verfĂŒgen ĂŒber Besonderheiten in ihrer Struktur, die fĂŒr die Interaktion mit anderen Proteinen notwendig sind [14,15].…”
Section: Struktur Und Expressionunclassified
“…B. MatrixMetalloproteinasen (MMP) oder "vascular endothelial growth factor" (VEGF; [11]). Ob jedoch ausschließlich ĂŒber homophile Proteinkomplexe Signalwege in Zellen aktiviert werden können oder EMMPRIN auch ĂŒber heterophile Interaktionen mit weiteren ZelloberflĂ€chen-rezeptoren Signaltransduktionen auslöst, konnte bislang nicht abschließend gezeigt werden [11,12,15].…”
Section: Funktionelle Eigenschaften Und Assoziierte Proteineunclassified
“…Discovered 25 years ago, this molecule was initially identified as a tumor surface protein capable of inducing matrix metalloproteinase (MMP) and named as tumor-cell derived collagenase stimulatory factor (TCSF). [3][4][5] While increased expression of CD147 occurs in many tumors, it's expression is not limited to tumor cells. CD147, a pleiotropic molecule critical in fetal development and retinal function, also has been shown to play a role in thymic T cell development and many neurological processes including the development of the nervous system, involvement in spatial learning and Alzheimer's plaque formation.…”
mentioning
confidence: 99%